The Phenomenon of Violence Against Educators and Education Personnel from the Perspective of Islamic Law - Muhibbuthabry, Muhibbuthabry; M. Yasin, Taslim; Dina, Diva (Riwayat: Educational Journal of History and Humanities, 2024)
The phenomenon of violence against educators and education personnel has become a concerning issue in the educational environment. In the perspective of Islamic Law, this violence not only violates social norms, but also contradicts Islamic principles that emphasize respect and protection for individuals, especially those who play a role in educating the next generation. This study aims to analyze the phenomenon of violence against educators and education personnel from the perspective of Islamic Law. This study uses a Descriptive Method that emphasizes the phenomenon of violence that occurs, both in schools, madrasas and the scope of education in general. The data obtained is based on actual data from interviews with responsible parties within the scope of the education unit. Violence in the world of education, both physical and psychological, has increased along with the aggressiveness of students, such as acts of beating and harassment. In Islamic law, violence is considered haram because it violates humanitarian principles and can be categorized as jarimah that is punishable according to the level of violation.